ADVERTISING VIDEO AS A SYNTHESIS OF MEDIA: UKRAINIAN WARTIME REALITIES - ДІДЕНКО, О. М. (Art and Design, 2024)
Methodology of the study of Ukrainian advertising was conducted using a historical and cultural approach, which allowed us to trace its development in the context of the war. The socio-cultural approach revealed a change in narrative and visual strategies used in advertising, and the comparative approach allowed us to compare Ukrainian advertising content with international standards. The article provides a detailed analysis of Ukrainian advertising and social videos and film clips in the context of of the war. The change in narrative and visual strategies used to engage the audience, in particular through patriotism, is investigated. to engage the audience, in particular through patriotic and social themes, as well as donor campaigns to support the army and the economy. The focus is on technological advances in the field of visual culture, which allows us to compare Ukrainian advertising content with international standards. The article focuses on on two key aspects: funding and donations for victory and support for Ukrainian services through display advertising. Examples of of modern Ukrainian commercials that contribute to the formation of new standards in the field of design and advertising. Scientific novelty of the article lies in the first analysis of the specifics of advertising content production under martial law, which emphasises its martial law, which emphasises its impact on the formation of national consciousness and support of the Ukrainian economy. The study provides new knowledge to young designers and scientists about the use of advertising and social video and film clips in the modern Ukrainian media space, which contributes to their professional development.